Pembacaan QS. Al-Nas (114): 4-5 dan Konsep Original Sins (Analisis The Quran and The West Karya Kenneth Cragg) - Dzakiy, Ahmad Farih; Mufid, Abdul; Masuwd, Mowafg (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
AbstractThis study investigated Surah Al-Nas verses 4-5, which describe the concept of original sin in Christianity and compare it to the concept of original sin in Islam. This study employed the Qur'anic text analysis approach and compared it to Kenneth Cragg's ideas in his book The Qur'an and the West. The Qur'anic text analysis method was utilized to thoroughly understand the verse's content. In contrast, Cragg's thought approach examines the perceived concept of original sin in Western tradition. The outcomes of this study demonstrate a fundamental distinction between the concept of original sin in Christianity, which regards sin as an inheritance from Adam, and the concept in Islam, which emphasizes individual responsibility for one's acts. This study adds to the knowledge of the fundamental distinctions between the two major religious traditions in their views on the original sin and their recognition of the human concept of God.Keywords: Original sin; Religious Understanding; The Qur’an and The West. AbstrakPenelitian ini bertujuan untuk menganalisis Surah Al-Nas ayat 4-5 yang menggambarkan konsep dosa asal dalam agama Kristen, dan membandingkannya dengan konsep dosa asal dalam Islam. Penelitian ini menggunakan pendekatan analisis teks al-Qur'an dan membandingkannya dengan pemikiran Kenneth Cragg dalam bukunya The Qur’an and The West. Metode analisis teks al-Qur'an digunakan untuk memahami makna ayat secara mendalam, sedangkan pendekatan pemikiran Cragg digunakan untuk melihat bagaimana konsep dosa asal dipahami dalam tradisi Barat. Temuan penelitian ini menunjukkan perbedaan mendasar antara konsep dosa asal dalam agama Kristen, yang menempatkan dosa sebagai warisan Adam, dengan konsep dalam Islam, yang tekanan tanggung jawab individu atas perbuatannya sendiri. Penelitian ini memberikan kontribusi pada pemahaman kita tentang perbedaan esensial antara dua tradisi agama besar dalam pandangan terhadap asal mula dosa dan kesadarannya terhadap pemahaman manusia tentang dasar-dasar dengan Tuhan. Kata Kunci: Dosa Asal; Pemahaman Agama; The Quran and The West.